An Analysis on the Implementation of Posbindu PTM Program at Beringin Raya Community Health Center Bengkulu - Oktarianita Oktarianita; Nopia Wati; Henni Febriawati; Afriyanto Afriyanto (Universitas Ahmad Dahlan, 2020)
Background: The implementation of Integrated Health Post or Pos Binaan Terpadu (Posbindu) Program for Non-Communicable Diseases is an effective and efficient strategy to control risk factor. The low interest in visiting Posbindu was shown from the number of visits that decreased in 2017 (75.4%) and 2018 (64.4%). This study aims to analyze the Integrated Health Post for Non-Communicable Diseases or Pos Binaan Terpadu Penyakit Tidak Menular (Posbindu PTM) program at Beringin Raya Community Health Center in Bengkulu. Method: This study used qualitative and descriptive approach, and was conducted in March-August 2020 using in-depth interview techniques. Results: The implementation of the Posbindu program was in accordance with the Standard Operating Procedures (SOP). Funding for this program came from the Health Operational Assistance. However, it was not sufficient. Posbindu activities were held once a month and used 5 steps system (registration, health interviews, health checks, referrals, and health education). The examination results was only recorded on the visiting book, and they did not have specific monitoring tools. The supervision of the implementation and the evaluation were discussed in the monthly mini workshop. In addition, the facilities and infrastructure were still inadequate. There was a shortage medicine supplies, and the community participation in Posbindu PTM was still low. Conclusion: Posbindu PTM has been implemented according to the SOP, but the overall implementation such as funding, drug procurement, infrastructure, and the number of Posbindu visits is still insufficient.